Consumer Behavior Trigger in Purchase Decision at PT Tirta Mumbul Jaya Abadi - I Gusti Made Oka Astana (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to determine the effect of product quality, brand image and service quality on purchasing decisions for bottled water products at PT Tirta Mumbul Jaya Abadi (Yeh Buleleng). A qualitative approach is used in this research. Data collection was carried out in this study using a technique in the form of a questionnaire with a measuring instrument in the form of a Likert scale with intervals of 1 to 5 where all 75 shops were selected as respondents selling products (Yeh Buleleng) in Singaraja. Determination of the sample of respondents in this study using non-probability sampling and the method used in this sampling is purposive sampling. Data analysis was performed using SPSS which included multiple linear regression analysis, normality analysis, multicollinearity, heteroscedasticity, coefficient of determination test, simultaneous F-test, and T-test, with a significance level of 5%. All relationships in the research studied showed positive and significant results related to product quality, brand image and service quality on purchasing decisions. Thus it can be concluded that (1) the better the quality of the product, the higher the decision to purchase water at PT. Tirta Mumbul Jaya Abadi (Yeh Buleleng) (2) the better the brand image of the product, the higher the decision to purchase water at PT. Tirta Mumbul Jaya Abadi (Yeh Buleleng) (3) the better the service quality, the higher the decision to buy water at PT. Tirta Mumbul Jaya Abadi (Yeh Buleleng).